KAJIAN QABDH DALAM TRANSAKSI EMAS DIGITAL (PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF) - Muhammad Al Adib Habibul Haq (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
This research discusses digital gold transactions in Indonesia which are growing rapidly along with the digitalization of the financial sector, with a focus on the validity of qabdh in the perspective of Islamic law. The main objective of this research is to understand the implications of Islamic law on the validity of qabdh in digital gold transactions as well as the application of the concept of ???urriyat al-ta???arruf in digital gold products. This research uses a qualitative method with a library research and conceptual approach, namely by reviewing the literature and formulating relevant legal concepts. The data used consists of primary legal materials, such as the Qur'an, Hadith, Fatwa DSN-MUI, POJK, Regulation of the Minister of Trade and scholars' opinions; as well as secondary legal materials in the form of books, journals, articles, and other scientific sources that support the study. The analysis technique used is content analysis by deeply examining the substance of related literature. The results show that the validity of qabdh in digital gold is acceptable in Islamic law as long as it fulfills sharia principles, including legal ownership and the right to use or transfer the asset, as regulated in the concept of hurriyat al-tasarruf.